Analisis Keunggulan dan Hambatan Implementasi Akad Al-Qardh dalam Lembaga Keuangan Syariah di Indonesia - Maylaffayzza Rahma Asyiffa; Shandika Yuma Ramadhani; Muhammad Zulfikar Abdul Aziz; Kholilur Rahman (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Al-qardh is a fundamental instrument in Islamic economics grounded in the principle of ta’awun (mutual assistance) and free from riba. This study aims to analyze the concept of Al-qardh based on the normative foundations of the Qur’an and Hadith, as well as its relevance in the modern context. Using a library research method with a content analysis approach to relevant literature, the study finds that Al-qardh is not merely a financial transaction but also a manifestation of moral responsibility and social solidarity. However, a gap exists between its normative ideals and contemporary implementation, particularly in the form of administrative costs and operational constraints. The findings indicate that Al-qardh is based on principles of justice, transparency, and accountability as reflected in Surah Al-Baqarah: 282 and Surah Al-Hadid: 11. Therefore, strengthening institutional frameworks and integrating social Islamic funds are necessary to maintain the social essence of Al-qardh in modern financial systems.